Novel CDKL5 mutations were found in patients in China: retrospective investigation in cases of CDKL5-related disorders - Yumei Yan; Dake He; Jing Wu; Ruolin Hou; Kun Sun; Ling Li (BMC, 2020)
Abstract Objective CDKL5-related disorders (CDD) is an epileptic encephalopathy resulted of gene mutations of CDKL5. This study aimed to explore the development process of CDD and to expand its mutation spectrum. Methods Clinic datawas collected about three infantile epileptic encephalopathy cases diagnosed at Xinhua Hospital Affiliated to Shanghai Jiaotong University, School of Medicine. Next generation sequencing technology was used to find three de novo mutations of CDKL5. We searched published literatures about CDKL5 in pubmed and made an analysis about our clinic data and the related literatures. Results The three patients were all girls. Their average onset age of seizures was around 2 months, and all of them have intractable epileptic seizures, severe intellectual disability, and hypotension. Among them, two presented infantile spasm and high arrhythmia in EEG, and the other manifested clonic seizure and broad epileptiform discharge in EEG. Extracerebral space widening in cranial MRIs was demonstrated in two cases. Visual evoked potential was abnormal in two cases. Seizures were resistant to all kinds of antiepileptic drugs (AEDs). Gene tests showed three de novo mutations of CDKL5: one was a truncated mutation (c.2254A > T,P.R752X, stop279), which was pathogenic according to the ACMG guide, the other two were missense mutations (c.377G > T,p.Cys126Phe) and a frameshift mutation (c.362-362insG(p.Ala122GlyfsTer7), which were likely pathogenic according to the ACMG. Conclusions All three de novo mutations are first reported. Based on the combined related literature and the manifestations observed, we diagnosed the three children as CDKL5-related disorders, and concluded that the de novo CDKL5 mutations are the reason for their epilepsy.